Analysis of the Application of Artificial Intelligence in the Neighbouring Countries According to the Government Artificial Intelligence Readiness Index - Momtshyan, Ani; Karapetyan, Aram (ՀՀ ԳԱԱ)
In today's rapidly developing world, many branches of the economy are trying to adapt to new technologies and automate as many processes as possible. Today, we are witnessing the rise of new technologies, with artificial intelligence (hereinafter referred to as AI) as the driver of software and the spearhead of the fourth industrial revolution. In the context of the current developments in the field of AI, we emphasize the multifaceted study of the policies conducted by the countries of the region (Armenia, Georgia, Azerbaijan, Turkey, Iran, hereinafter referred to as the CR countries) in order to reveal the degree of digitization of their economies, the directions of the main application of AI, the results obtained from political initiatives, AI risks and opportunities, obstacles and reasons for their occurrence. Ժամանակակից արագ զարգացող աշխարհում տնտեսության շատ ճյուղեր փորձում են հարմարվել նոր տեխնոլոգիաներին և ավտոմատացնել հնարավորինս շատ գործընթացներ: Այսօր մենք նոր տեխնոլոգիաների վերելքի ականատեսն ենք, որում որպես ծրագրային ապահովման շարժիչ և չորրորդ արդյունաբերական հեղափոխությունն առաջ մղող հանդես է գալիս արհեստական բանականությունը (այսուհետ՝ ԱԲ): В современном быстро развивающемся мире многие отрасли экономики пытаются приспособиться к новым технологиям и максимально автоматизировать процессы. Сегодня мы наблюдаем появление новых технологий с искусственным интеллектом (ИИ) в качестве драйвера программного обеспечения и движущей силы четвертой промышленной революции. В контексте текущих событий в области ИИ подчеркнем многогранное изучение политики, проводимой странами региона (Армения, Грузия, Азербайджан, Турция, Иран, далее страны СР) с целью выявления степени цифровизации их экономик, направления основного применения ИИ, результаты, получаемые от политических инициатив, ИИ-риски и возможности, препятствия и причины их возникновения.
Keywords: Social and Humanitarian Sciences